ENHANCING DESCRIPTIVE WRITING COMPETENCE VIA PROJECT-BASED LEARNING AND GALLERY WALK ACTIVITY TITLE OF PAPER - Vincha, Villia; Astutik, Indri; Oktarini, Widya (English Education Study Program STKIP PGRI Pacitan, 2025)
Mastering the skill of writing is often regarded as the most challenging task for students. Therefore, it is important to conduct research to improve students’ writing skills. This study employed a classroom action research (CAR) design to enhance students’ writing proficiency by integrating the Project-Based Learning model and Gallery Walk activity. The subjects of this study were the 17 students of 7-A grade at SMPN 02 Ledokombo. Data were collected using writing tests, interviews, and observation sheets. The average formula was used to analyse the data from students’ writing tests. The collaboration between Project-Based Learning and Gallery Walk activity significantly impacted the students' learning process. All of the students were active and enthusiastic during learning, and they could exchange knowledge to solve problems. This led to the results of Cycle II meeting the criteria for success. Project-Based Learning and Gallery Walk activity enhanced students’ writing skills across two cycles, improving from a score of 71.5 in Cycle I to 84.7 in Cycle II, surpassing the Minimum Passing Mark of ≥78. Based on the results, the implementation of the Project-Based Learning model with Gallery Walk activity as a method to improve students' writing skills in descriptive text was successful